Peran Pemerintah Dalam Mengurangi Kemiskinan - Harefa, Putri Amalia (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Medan Labuhan District, is one of the sub-districts in North Medan. Nelayan Indah Village is one of the villages in Medan Labuhan District. In this area most of the people live below the poverty line. Therefore, Medan City Regional Regulation Number 5 of 2015 was issued concerning Poverty Reduction. The purpose of this study is to find out how the government's role in implementing the Medan City Regional Regulation Number 5 of 2015 article 14 concerning Poverty Reduction and what are the government's obstacles. The problem formulation of this research is how is the role of the government in implementing the Medan City Regional Regulation Number 5 of 2015 article 14 concerning Poverty Reduction and what are the government's obstacles in implementing the Medan City Regional Regulation Number 5 of 2015 concerning Poverty Alleviation. The results of this study are that the government implements poverty reduction programs, namely, food assistance (BANSOS, BLT, BPNT), health assistance (PKH Health), educational assistance (PKH Pendidikan), housing assistance (house renovation), skills improvement assistance (sewing) , business capital assistance (UMKM), security protection assistance (KAMTIBMAS). Then the government's obstacles are the inaccurate data collection and program targets, the community is less active, and the aid is used consumptively.